2017
DOI: 10.1002/jcb.26069
|View full text |Cite
|
Sign up to set email alerts
|

Erdj3 Has an Essential Role for Z Variant Alpha‐1‐Antitrypsin Degradation

Abstract: Alpha‐1‐antitrypsin deficiency (AATD) is an inherited disease characterized by emphysema and liver disease. AATD is most often caused by a single amino acid substitution at amino acid 342 in the mature protein, resulting in the Z mutation of the alpha‐1‐antitrypsin gene (ZAAT). This substitution is associated with misfolding and accumulation of ZAAT in the endoplasmic reticulum (ER) of hepatocytes and monocytes, causing a toxic gain of function. Retained ZAAT is eliminated by ER‐associated degradation and auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…ERdj3, a canonical co-chaperone, is known to efficiently secrete to the extracellular space because of ER stress and seems to protect the extracellular environment from potentially toxic (29). ERdj3 binds misfolded proteins such as ZAAT in the ER of hepatocytes (6,30). We showed that ERdj3 also binds to calreticulin, the ER-resident lectin chaperone, with the capacity for binding to ZAAT within the ER of hepatocytes (6).…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…ERdj3, a canonical co-chaperone, is known to efficiently secrete to the extracellular space because of ER stress and seems to protect the extracellular environment from potentially toxic (29). ERdj3 binds misfolded proteins such as ZAAT in the ER of hepatocytes (6,30). We showed that ERdj3 also binds to calreticulin, the ER-resident lectin chaperone, with the capacity for binding to ZAAT within the ER of hepatocytes (6).…”
Section: Discussionmentioning
confidence: 78%
“…Secreted ERdj3 can bind misfolded substrates and prevent their extracellular aggregation (17). Our previous studies revealed that ERdj3 competes with calreticulin when binding to ZAAT and delays ZAAT degradation (6). We extended these experiments using small interfering RNA against calreticulin (siCALR) to follow the ZAAT trafficking pathway.…”
Section: Calreticulin Depletion Increases the Extracellular Level Of mentioning
confidence: 98%
See 3 more Smart Citations